The search for mathematical roots, 1870-1940: logics, set theories and the foundations of mathematics from Cantor through Russell to Gödel. - Grattan-Guinness, I; Grattan-Guinness, I (Princeton University Press, 2001)
While many books have been written about Bertrand Russell's philosophy and some on his logic, I. Grattan-Guinness has written the first comprehensive history of the mathematical background, content, and impact of the mathematical logic and philosophy of mathematics that Russell developed with A. N. Whitehead in their Principia mathematica (1910-1913).